Where Internationalization and Innovation Meet: A Study on Portuguese SMEs - Martins, Nayra (2022)
The aim of this study is to analyze the interdependencies between internationalization and innovation processes of Portuguese SMEs, identifying the main barriers that hurdle it. For this study two types of primary data were used. A questionnaire was applied to the 8100 Portuguese companies selected from the AICEP (Portuguese Agency for investment and External Trade) data base, from which 310 valid responses were obtained. Furthermore, 24 case study of Portuguese firms were used, to access different types of data. IBM SPSS Statistics 26.0 and Nvivo 12 were used for data analysis. [...]